SALIDUMMAY’S HYBRIDITY AND CONGREGATIONAL SINGING - Reyes, Michiyo Yoneno (Humanities Diliman: A Philippine Journal of Humanities, 2010)
A group of songs called salidummay, popular in Northern Philippine highlands, is characterized by musical features of Anglo-American folk songs epitomized by meter and anhemitonic pentatonic pitch system (against domination of two to four tone tunes of older chants), as well as vernacular lyrics that often carry the formulaic expressions of older chants of the locale. The paper asks why salidummay songs that present hybrid features than other local forms have become a symbol of collective identity of the peoples of Northern Luzon highlands as that of the “Cordillera.” Analysis of three salidummay renditions performed in two privately hosted communal feasts (palanos) of the Banaos at western Kalinga reveals the categorical inconsistency of salidummay songs that carry both features of premodernity (spontaneity, orality, intimacy of communal reception) and modernity that is ultimately attributed to “congregational singing.” The paper then argues that the simultaneity of congregational singing of hymn singing , that is applied today to the singing of anthems, martial songs and protest songs, is the praxis of modernity; that it has already become the habitus of Filipinos in the twentieth century; and that, thus, salidummay singing is believed to be “tradition” in the narrative of projecting ethnicity. The paper concludes that tempo-spatial strata of premodernity and modernity is the key to understanding the sociocultural complex of contemporary Philippines.
Keywords: salidummay, Cordillera, modernity, singing, American-colonial